2018
DOI: 10.5114/ms.2018.76878
|View full text |Cite
|
Sign up to set email alerts
|

The roles of vaspin, chemerin, and omentin in the determination of metabolic syndrome

Abstract: Metabolic syndrome (MetS) is defined as multiple risk factors including abdominal obesity, dyslipidaemia, abnormal glycaemia, and elevated blood pressure. The incidence of MetS and pathophysiological mechanisms underlying its development are still not fully understood. It is thought that the occurrence of MetS arises from the complex relationship between genetic and environmental factors. The aim of the study was to overview and summarise current knowledge regarding genetic determinants of MetS. Also analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 171 publications
(243 reference statements)
0
6
0
Order By: Relevance
“…In obese teenagers serum omentin-1 levels were significantly lower in the MetS group compared to the group without MetS (289.5 ±51.9 ng/ml vs. 268.2 ±60 ng/ml), although omentin did not show statistically significant correlations with abnormal glucose metabolism indicators [12]. Stejskal et al found that omentin-1 serum levels were significantly lower in patients with premature coronary artery disease (103.1 ±62.7 mg/l) compared to MetS (668.2 ±339.6 mg/l) and healthy subjects (623.0 ±373.5 mg/l) [31,32]. The results of research conducted by Kilic et al showed that although the plasma omentin-1 concentrations were correlated with high triglyceride and low HDL-C levels, which are two of the five metabolic syndrome indicators, the plasma omentin-1 concentrations are similar in MetS subjects and individuals in the healthy control group [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In obese teenagers serum omentin-1 levels were significantly lower in the MetS group compared to the group without MetS (289.5 ±51.9 ng/ml vs. 268.2 ±60 ng/ml), although omentin did not show statistically significant correlations with abnormal glucose metabolism indicators [12]. Stejskal et al found that omentin-1 serum levels were significantly lower in patients with premature coronary artery disease (103.1 ±62.7 mg/l) compared to MetS (668.2 ±339.6 mg/l) and healthy subjects (623.0 ±373.5 mg/l) [31,32]. The results of research conducted by Kilic et al showed that although the plasma omentin-1 concentrations were correlated with high triglyceride and low HDL-C levels, which are two of the five metabolic syndrome indicators, the plasma omentin-1 concentrations are similar in MetS subjects and individuals in the healthy control group [14].…”
Section: Discussionmentioning
confidence: 96%
“…Studies on the expression and polymorphisms of omentin genes in relation to metabolic risk factors are among the few. In the available literature, the relationship between omentin gene polymorphisms and MetS risk as a syndrome has not been analysed so far [32]. The influence of omentin polymorphism on MetS and its components can therefore only be concluded indirectly, analysing the association of this polymorphism with the prevalence of other diseases such as obesity, as well as type 2 diabetes, non-alcoholic fatty liver disease (NAFLD), and coronary artery disease (CAD), for which MetS is a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Given the conflicting data about the pathophysiologic mechanisms linking between adipokines including chemerin and NAFLD, a precise determination of their role in NAFLD is mandatory. Consequently, it may be used as noninvasive biomarkers for the diagnosis of NAFLD and interventions aiming at modulating their levels may result in its use as a novel target in NAFLD therapy (34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…Vaspin (visceral adipose tissue-derived serine protease inhibitor) was isolated for the first time from visceral adipose tissue in Otsuka Long-Evans Tokushima Fatty rats, which comprises an animal model of abdominal obesity, accompanied by type 2 diabetes mellitus (T2DM) [1]. Human vaspin mRNA has been found both in the visceral and in subcutaneous adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It is coded by the gene SERPNA12 located on the long arm of chromosome 14 (14q32.13) and consists of five introns and six exons. According to the literature review, there is a positive association between the vaspin concentration in the blood serum and the indicators of obesity, T2DM, polycystic ovary syndrome (PCOS) and coronary artery disease (CAD) [1,2]. Feng et al .…”
Section: Introductionmentioning
confidence: 99%